KEWENANGAN FORMIL & MATERIIL DALAM PENGAWASAN DAN PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI MALAYSIA SEBAGAI LEX POSTERIOR TERHADAP PERAN PEMERINTAH DAN LEMBAGA INDEPENDEN - Iron Sarira (Mimbar Hukum, 2023)
Abstract The Covid-19 pandemic has had a significant impact on various business fields, including related to employment. Many terminations of employment, due to the weakening of the economy which then has an impact on workers who have lost their income. One of them is becoming a Migrant Worker to work in Malaysia. Procedures related to the Protection of Indonesian Migrant Workers are regulated in Law Number 18 of 2017 as a protection for the community against human trafficking, slavery, forced labor, workplace violence, and crimes against human dignity. Legal certainty is an issue discussed in this paper related to an implementation perspective, namely positive law as lex posteriori in the aspect of law enforcement, as well as a regulative perspective, namely differences in formal and material procedures related to the role of Supervisory and Independent Bodies, as the implementer of PPMI policy. This research is about normative juridical with a literature review which will be analyzed with scientific aspects of law in economics. This study uses the line of equality method in looking at formal and material authority over PPMI governance following positive law as lex posterior and a legal approach philosophically (value and intensity) as an effort to realize the aspired law (ius constituendum). Abstrak Pandemi Covid-19 telah memberikan dampak signifikan ke berbagai bidang usaha, termasuk bidang ketenagakerjaan. Banyak terjadi pengakhiran hubungan kerja karena melemahnya perekonomian yang kemudian berdampak bagi pekerja yang kehilangan penghasilannya. Salah satunya adalah menjadi Pekerja Migran untuk bekerja di Malaysia. Pengaturan Perlindungan Pekerja Migran Indonesia dalam Undang-Undang Nomor 18 Tahun 2017 sebagai perlindungan negara kepada masyarakat dari adanya perdagangan manusia, perbudakan, kerja paksa, kekerasan kerja, dan kejahatan atas harkat dan martabat manusia. Kepastian hukum merupakan tujuan dari diangkatnya permasalahan dalam penulisan ini terkait adanya perspektif implementatif, serta perspektif regulatif, yakni perbedaan pengaturan formil dan meteriil terkait adanya peran Pengawas dan Badan Independent pelaksana kebijakan PPMI. Penulisan yuridis normatif dengan kajian literatur ini akan dianalisis dengan aspek keilmuan hukum dalam ekonomi yang menggunakan metode line of equality dalam melihat kewenangan formil dan materiil terhadap tata kelola PPMI sesuai dengan hukum positif sebagai lex posterior serta pendekatan hukum secara filosofis (nilai dan intensitas) sebagai upaya mewujudkan hukum yang dicita-citakan (ius constituendum).